The Effect Of Work Behavior And Work Environment On Employee Performance - Septiyana Harti Sugma (Islamic University of Kalimantan MAB Banjarmasin, 2022)
Employees in an organization were integral to the organization's success. High-performing employees were able to advance the organization to the highest level. The performance standards for competent individuals were quality, quantity, efficiency, and effectiveness, in addition to the ability to collaborate with coworkers. The purpose of this investigation was to determine the impact of employee behavior and work environment on employee performance. This research employs a quantitative verification technique. This survey included all KJP Sugianto Prasadjo personnel from all branches including the main office. This research sample consists of 100 KJP Sugianto Prasadjo employees. Purposive sampling was used for the sample process. Sugianto Prasadjo administered a statement questionnaire to 100 KJP employees as the tool. The research data were analyzed using version 3.0 of Smart PLS. Work conduct had a significant effect on employee performance (p<0.05), the work environment had a significant effect on employee performance (p<0.05), and the work environment mediated the effect of work behavior on employee performance (p<0.05). Consequently, employee performance was influenced by behavior and the working environment. It was anticipated that future study will be able to establish a performance improvement model to foster innovative employee work behaviors for the benefit of the organization